Association of Rare Recurrent Copy Number Variants With Congenital Heart Defects Based on Next-Generation Sequencing Data From Family Trios - Liu, Yichuan; Chang, Xiao; Glessner, Joseph; Qu, Huiqi; Tian, Lifeng; Li, Dong; Nguyen, Kenny; Sleiman, Patrick M. A.; Hakonarson, Hakon (Frontiers in Genetics, 2019)
Congenital heart defects (CHD) are a common birth defect, affecting approximately 1% of newborn children in the United States. As previously reported, a significant number of CHD are potentially attributed to altered copy number variations (CNV). However, as many genomic variants are rare, a large scale CNV triad study is necessary to characterize the genetic architecture of CHD. We used whole exome sequencing (WES) data generated by the Pediatric Cardiac Genomics Consortium (PCGC), including a discovery data set of 2,103 individuals from 760 nuclear family trios, and an independent replication set of 4,808 individuals from 1,712 trios. The candidate targets uncovered were further validated through different platforms, including the OMNI SNP array chip in 1,860 individuals and the whole genome sequencing (WGS) data in 33 trios. The genes harboring CNVs of interest were then investigated for expression alternations based on cardiac tissue RNA-seq data. We identified multiple CNVs in the WES data that associated with specific sub-phenotypes of CHD in approximately 2,400 families, including 98 de novo CNV regions. We identified five CNV loci harboring LIMS1, GCC2, RANBP2, TTC3 and MAP3K7CL, respectively, where those genes are highly expressed in human heart and/or mouse embryo heart at 15 days. Five novel CNV loci were uncovered demonstrated altered expression of the respective candidate genes involved. To our knowledge, this is the largest trio-based WES study of CHD and in addition to uncovering novel CHD targets, presents an extensive resource with the potential to provide important insights to the architecture and impact of CNVs in CHD.